2021
DOI: 10.1186/s12885-021-07823-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of irinotecan and oxaliplatin as the first-line therapies for metastatic colorectal cancer: a meta-analysis

Abstract: Background Irinotecan (IRI) and oxaliplatin (Ox) are standard therapeutic agents of the first-line treatments for metastatic colorectal cancer (mCRC). Previous meta-analyses of randomized controlled trials (RCTs) showed that treatment with Ox-based compared with IRI-based regimens was associated with better overall survival (OS). However, these reports did not include trials of molecular targeting agents and did not take methods for the administration of concomitant drugs, such as bolus or cont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 46 publications
4
14
0
Order By: Relevance
“…When comparing first-line therapies combined with bevacizumab, the group of patients treated with irinotecan-based chemotherapy had better median OS as compared to the oxaliplatin group (24 vs. 21 months respectively). However, these findings were not statistically significant and are consistent with Kawai’s recent meta-analysis that demonstrated that these two regimens are similar in terms of OS [ 20 ]. Notably, we found that patients who received more administrations of bevacizumab experienced longer OS.…”
Section: Discussionsupporting
confidence: 78%
“…When comparing first-line therapies combined with bevacizumab, the group of patients treated with irinotecan-based chemotherapy had better median OS as compared to the oxaliplatin group (24 vs. 21 months respectively). However, these findings were not statistically significant and are consistent with Kawai’s recent meta-analysis that demonstrated that these two regimens are similar in terms of OS [ 20 ]. Notably, we found that patients who received more administrations of bevacizumab experienced longer OS.…”
Section: Discussionsupporting
confidence: 78%
“…However, this group included patients with poor performance status and the treatment was given as a salvage regimen. On the other hand, there was no difference in PFS between FOLFIRI and FOLFOX, comparable to the literature 12 …”
Section: Discussionsupporting
confidence: 89%
“…Mutations in UGT genes in the tumor that reduce the glucuronidation of anticancer drugs can increase intratumoral drug concentrations, thus potentially enhancing therapy efficacy and inhibiting tumor growth. For example, irinotecan is commonly used for treating colorectal cancer (COAD), and its active metabolite, SN-38, is primarily glucuronidated by UGT1A1 with weak activity from all other UGT1As except UGT1A4 [ 101 , 102 , 103 , 104 , 105 ]. We recently showed the expression of all nine UGT1As at varying levels in COAD tumors, suggesting that there is in situ glucuronidation of SN-38 within the tumor [ 39 ].…”
Section: Discussionmentioning
confidence: 99%